2021
DOI: 10.4081/aiua.2021.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Age above 70 years and Charlson Comorbidity Index higher than 3 are associated with reduced survival probabilities after radical cystectomy for bladder cancer. Data from a contemporary series of 334 consecutive patients

Abstract: Objective: To assess the joint effect of age and comorbidities on clinical outcomes of radical cystectomy (RC).Methods: 334 consecutive patients undergoing open RC for bladder cancer (BC) during the years 2005-2015 were analyzed. Pre-, peri- and post-operative parameters, including age at RC (ARC) and Charlson Comorbidity Index (CCI), were evaluated. Overall and cancer-specific survivals (OS, CSS) were assessed by univariate and multivariate modelling. Furthermore, a three-knot restricted cubic spline (RCS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(17 reference statements)
1
4
1
1
Order By: Relevance
“…Moreover, cT3 and cT4a patients had an extremely poor prognosis, with a median survival of about 313-414 days due to inadequate treatment. On the other hand, although a high CCI (≥3) and older age were not poor prognostic factors in this study, Maffezzini et al (17) reported that RC worsened the prognosis in patients older than 70 years and with a high CCI (>3). In view of this, the survival benefits, and the disadvantages of treatment-related complications associated with DT, should be carefully considered when the patients with reduced physical function choose DT.…”
Section: Discussioncontrasting
confidence: 72%
“…Moreover, cT3 and cT4a patients had an extremely poor prognosis, with a median survival of about 313-414 days due to inadequate treatment. On the other hand, although a high CCI (≥3) and older age were not poor prognostic factors in this study, Maffezzini et al (17) reported that RC worsened the prognosis in patients older than 70 years and with a high CCI (>3). In view of this, the survival benefits, and the disadvantages of treatment-related complications associated with DT, should be carefully considered when the patients with reduced physical function choose DT.…”
Section: Discussioncontrasting
confidence: 72%
“…The association between some preoperative characteristics of the patients and rates of complications were previously reported in the literature (30,31). The association between perioperative hypoalbuminemia and risk of wound infection was also reported by other authors (32).…”
Section: Discussion and Conclusion Remarkssupporting
confidence: 58%
“…In the study by Koppie et al, overall survival was demonstrated decreasing in patients with high comorbidity considering the comorbidity index, but recurrence-free survival was not affected. Again Maffezini et al In his study, a CCI of more than 3 was found to be associated with survival (16). It is also noteworthy that patients with high comorbidities had been performed less lymph node dissection and less postoperative chemotherapy (9).…”
Section: Discussionmentioning
confidence: 84%